When Do Investors Value Key Audit Matters?. Issue 1 (1st January 2021) - Moroney, Robyn; Phang, Soon-Yeow; Xiao, Xinning
Abstract: While prior studies have considered the effect of the enhanced auditor's report (EAR) on a range of auditor, management and investors' judgments, we consider whether the inclusion of key audit matters (KAMs) in the EAR affects investor perceptions of the value of the audit as well as the credibility of the auditor. These are important issues linked to the rationale for the introduction of the EAR. As prior studies have demonstrated that audit firm size affects investor perceptions across a range of measures, we predict that the link between KAMs (absent versus present) and investor perceptions around value and credibility is affected by audit firm size. We find that the inclusion of KAMs improves perceived value and credibility only when a Non-Big 4 firm conducts the audit. When a Big 4 firm conducts the audit, perceived value and credibility are high whether KAMs are included or not. We also find that perceived credibility mediates the joint effect of KAMs and audit firm size on the perceived value of the audit. In additional analysis, we find that the inclusion of KAMs draws investors' attention to new and expanded messages, taking their attention away from messages considered core to the audit report.